The European Union and its Political Leaders
X, 294 p.
Keywords: This book focuses on the impact of political leaders on the integration process led by the European Union. It aims at a better understanding of the European Union through the actions, contributions, and ideas of these outstanding characters to European integration and disintegration. By doing so, the book offers an entirely new perspective, presenting the actions of the main actors involved, their background, their historical time, their challenges and problems, and how they influenced the European Union's development. The authors in detail discuss different ideas connected to leaders, such as Jean Monnet and neo-functionalism, Spinelli and federalism or Churchill and the idea of cooperation. Furthermore, the book examines major policies and events, like the Common Agricultural Policy, the creation of the Euro as a consequence of the German reunification and Mitterrand’s reactions, or Brexit and its connection to the impact of Margaret Thatcher. The global essence of thebook makes it a must-read for students, researchers, and scholars interested in a better understanding of the European Union's integration process.